CRIMINALIZATION POLICY ON THE ACT OF MAKING, PRODUCING, AND TRADING ILLEGAL FISHING CAPTURE EQUIPMENT - Farida, Ida; Katimin, Herman (Faculty of Law Universitas Padjadjaran, 2023)
The widespread use of illegal fishing capture equipment in the form of drag nets and drag nets which harm and endanger the sustainability of fish resources and the environment in Indonesian waters, cannot be separated from the act of making, producing, and trading. The research method used is a sociological juridical approach which is qualitative in nature, where this research uses a normative approach with a sociological approach as support. Based on the results of the research, criminalizing the act of making, producing, and trading becomes a crime, formulated in article 85A, which reads